Chromosome-level genome assembly of Megachile lagopoda (Linnaeus, 1761) (Hymenoptera: Megachilidae) - Zhang, Dan; Jin, Jianfeng; Niu, Zeqing; Orr, Michael C.; Zhang, Feng; Ferrari, Rafael R.; Wu, Qingtao; Zhou, Qingsong; Da, Wa; Luo, Arong; Zhu, Chaodong (Scientific data, 2024)
Megachile is one of the largest bee genera, including nearly 1,500 species, but very few chromosome-level assemblies exist for this group or the family Megachilidae. Here, we report the chromosome-level genome assembly of Megachile lagopoda collected from Xizang, China. Using PacBio CLR long reads and Hi-C data, we assembled a genome of 256.83 Mb with 96.08% of the assembly located on 16 chromosomes. Our assembly contains 266 scaffolds, with a scaffold N50 length of 15.6 Mb, and BUSCO completeness of 99.20%. We masked 27.10% (69.61 Mb) of the assembly as repetitive elements, identified 459 non-coding RNAs, and predicted 11,157 protein-coding genes. This high-quality genome of M. lagopoda represents an important step forward for our knowledge of megachilid genomics and bee evolution overall.